The Effect of Addition Various Concentrations of Yeast (Saccharomyces cerevisiae) on the Quality of Porang Tubers (Amorphophallus sp.) - Wati, Ira; Helmi, Henny; Lingga, Rahmad (Universitas Sam Ratulangi, 2025)
Porang tubers (Amorphophallus sp.) are a food commodity rich in glucomannan but also contain antinutritional compounds such as calcium oxalate. This study aimed to determine the effect of adding Saccharomyces cerevisiae yeast on improving the quality of porang flour and its ability to reduce calcium oxalate content. The research method used was fermentation with the addition of various concentrations of S. cerevisiae. The treatments applied were soaking with 10% S. cerevisiae, 20% S. cerevisiae, and a control treatment without yeast (0%). Parameters observed during the fermentation process included pH, total acidity, and total population in the porang soaking water. Meanwhile, yield, calcium oxalate, glucomannan, starch, moisture, ash, and color were analyzed to assess porang flour quality. The results showed that pH decreased and total acidity increased with the length of fermentation up to 72 hours. Yeast increased at 10% and 20% S. cerevisiae concentrations until 48 hours and decreased at 72 hours, whereas in the control treatment, population of yeast decreased up to 48 hours and increased at 72 hours. The study indicated that fermentation with S. cerevisiae effectively reduced calcium oxalate content and improved porang flour quality. The lowest calcium oxalate content was found in the 10% S. cerevisiae treatment, while the highest glucomannan content was observed in the 20% treatment. Porang flour treated with 20% S. cerevisiae showed lower moisture and ash content, while flour from the 10% treatment had higher starch content and a brighter color. Based on various test parameters, the porang flour produced in this study complied good quality standards.